A Reversal of Fortunes: Daniel among the Scholars. (February 2018) - Merrill Willis, Amy C.
Scholarship on the book of Daniel has undergone a significant shift since the publication of K. Koch's groundbreaking work, The Rediscovery of Apocalyptic, in 1972. Despite significant achievements in understanding the historical-critical issues of the book, scholarship viewed Daniel's apocalyptic visions as embarrassing. The renaissance in Daniel studies that began in the 1970s has since produced a robust conversation and newer theory-driven insights around well-established areas of interest. These include Daniel's textual traditions and compositional history, the function of its genres, the social settings of its writers, and Daniel's near eastern literary and cultural milieu. New areas of interest identified in the landmark study of J.J. Collins and P.W. Flint (2001; 2002), namely the history of reception and political theologizing, have also gained ground. Daniel's reversal of fortunes is due to new methodologies as well as a fundamental paradigm shift in interpretation; this change has seen Daniel scholarship move away from the search for Daniel's historical meaning, narrowly construed, and toward the quest to understand what Daniel does to and for its readers.